Federal reserve interest rates, investment behavior, and arbitrage in exchange traded-funds - Sobati, Pegah; Koy, Ayben; Colak, Andac Batur (The Economics and Finance Letters, 2026)
This study investigates the influence of U.S. Federal Reserve interest rate policy on investor behavior, liquidity, and arbitrage efficiency in 29 iShares exchange-traded funds (ETFs) spanning large-, mid-, and small-cap benchmarks from 2013 to 2024. Using weekly data and econometric techniques combining time-series and panel approaches, the analysis incorporates key macroeconomic indicators, interest rates, the U.S. dollar index, economic activity measures, and market volatility to assess their combined effect on ETF market dynamics. Findings show that interest rate shifts significantly influence asset allocation, sector preferences, and risk tolerance, with higher rates often strengthening the dollar and increasing the appeal of fixed-income assets. Active trading is associated with narrower bid–ask spreads through enhanced liquidity, while passive investment widens spreads. ETF volatility is positively related to spreads, reflecting increased uncertainty and transaction costs in turbulent markets. The results provide empirical evidence on the behavioral channels linking monetary policy, market conditions, and trading efficiency, offering implications for policymakers, asset managers, and market participants. The major contribution of the study is to the empirical finance literature by integrating time-series and panel econometric methods to quantify the joint effects of interest rate policy, macroeconomic indicators, and investor sentiment on ETF market microstructure. Findings offer statistically robust insights into liquidity formation, volatility transmission, and arbitrage efficiency in diversified ETF markets.